2006
DOI: 10.1021/jp0612477
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Equilibrium of Bis(trifluoromethanesulfonyl) Imide Anion of a Room-Temperature Ionic Liquid:  Raman Spectroscopic Study and DFT Calculations

Abstract: The structure of bis(trifluoromethanesulfonyl) imide (TFSI-) in the liquid state has been studied by means of Raman spectroscopy and DFT calculations. Raman spectra of 1-ethyl-3-methylimidazolium (EMI+) TFSI- show relatively strong bands arising from TFSI- at about 398 and 407 cm(-1). Interestingly, the 407 cm(-1) band, relative to the 398 cm(-1) one, is appreciably intensified with raising temperature, suggesting that an equilibrium is established between TFSI- conformers in the liquid state. According to DFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

51
416
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(471 citation statements)
references
References 28 publications
51
416
2
2
Order By: Relevance
“…A change in the preferred conformer of the [Tf 2 N] À anion at the surface depending on the alkylchain length of the cation was recently found by K. Nakajima et al 36 This fact was considered by the choice of an ion pair with a syn-conformer of the anion for [EMIm]Tf 2 N and one with the respective anti-conformer is chosen for [OMIm]Tf 2 N (see the displayed structure of the two utilized ion pairs in Fig. 1 52 have shown that the syn-conformer of the anion exhibits a slightly higher energy than the anti-conformer. This energetic order is also present in our calculations.…”
Section: Calculation Methodsmentioning
confidence: 93%
“…A change in the preferred conformer of the [Tf 2 N] À anion at the surface depending on the alkylchain length of the cation was recently found by K. Nakajima et al 36 This fact was considered by the choice of an ion pair with a syn-conformer of the anion for [EMIm]Tf 2 N and one with the respective anti-conformer is chosen for [OMIm]Tf 2 N (see the displayed structure of the two utilized ion pairs in Fig. 1 52 have shown that the syn-conformer of the anion exhibits a slightly higher energy than the anti-conformer. This energetic order is also present in our calculations.…”
Section: Calculation Methodsmentioning
confidence: 93%
“…It was concluded that a conformational equilibrium indeed must exist between the C 1 and C 2 conformers of the [Tf 2 N] À ion in the liquid À ion, known also from crystal structures [166]. Figure adapted from Fujii et al [165] [C 2 mim][Tf 2 N]. The C 2 conformer is more favorable than the C 1 one [165].…”
Section: Other Systemsmentioning
confidence: 97%
“…In addition to these studies, the structure of the bis(trifluoromethylsulfonyl)imide ([Tf 2 N] À ) anion in the liquid state has been investigated by means of IR and Raman spectroscopy and ab-initio self-consistent Hartree-Fock and DFT calculations on the free ion, aiming at a determination of the equilibrium geometry and understanding of the vibrational spectrum [137,[163][164][165]. A pronounced delocalization of the negative charge on the nitrogen and oxygen atoms was found, and a marked double-bond character of the S-N-S moiety for the anion [163,164].…”
Section: Other Systemsmentioning
confidence: 99%
See 2 more Smart Citations